Early intervention to assist children with speech delay: parents must be aware - Dwi Pebrina Sinaga; Marlina Tampubolon; Nurul Husnah Harahap; Monika Sales Sitompul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
The Covid-19 pandemic and the rapid increase in children’s exposure to digital devices have contributed to a rising prevalence of speech delay in early childhood, primarily due to reduced social interaction and limited language stimulation. Despite growing attention to this issue, existing studies tend to examine causes, indicators, or interventions separately, with limited integration of developmental, environmental, and post-pandemic contexts. This study aims to analyze the phenomenon of speech delay in early childhood by identifying its developmental indicators, contributing risk factors in the post-Covid-19 era, and effective intervention strategies to support early language development. This research employed a qualitative library research method, analyzing 25 scientific sources published between 2010 and 2025, including peer-reviewed journal articles, academic books, and official reports. Data were analyzed using thematic analysis through systematic coding, categorization, and synthesis of key concepts related to speech delay. The findings indicate that speech delay is a multidimensional condition influenced by the interaction of genetic and environmental factors, particularly excessive screen time, limited communicative interaction, and inadequate language stimulation. Early detection of speech delay indicators and timely intervention are essential to prevent long-term communication difficulties. Effective intervention strategies include a combination of professional-based therapies, parent-mediated stimulation, and play-based approaches such as big book reading, storytelling using children’s work, and puppet-assisted storytelling. This study contributes theoretically by reinforcing a socio-developmental perspective on speech delay and practically by providing evidence-based insights for parents, educators, and practitioners to support early detection and intervention in early childhood communication development.